2014
DOI: 10.1007/s00213-014-3447-z
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of zopiclone 7.5 mg on highway driving performance in insomnia patients and healthy controls: a placebo controlled crossover study

Abstract: RationaleResidual effects of hypnotics on driving performance have been mainly determined in studies using a standardized driving test with healthy good sleepers. Responses to effects may differ, however, between insomniacs and healthy volunteers due to the underlying sleep disorder. In addition, a majority of insomniacs uses hypnotics chronically resulting in the development of tolerance to impairing effects. Impaired driving performance in healthy volunteers may then be an overestimation of the actual effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 39 publications
1
58
0
Order By: Relevance
“…On the other hand, a recent systematic review showed that pharmacotherapy, including augmentation therapy with antipsychotics, may reduce cognitive impairment in depressed patients . Antidepressants can improve driving performance in untreated patients with depression and administration of psychotropics, including antidepressants and hypnotics, can decrease a drug's influence on driving performance . Because we did not examine driving performance over time, further research is needed regarding the confounding of depression and pharmacotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, a recent systematic review showed that pharmacotherapy, including augmentation therapy with antipsychotics, may reduce cognitive impairment in depressed patients . Antidepressants can improve driving performance in untreated patients with depression and administration of psychotropics, including antidepressants and hypnotics, can decrease a drug's influence on driving performance . Because we did not examine driving performance over time, further research is needed regarding the confounding of depression and pharmacotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…The highway driving test (HDT) performed in the Netherlands was frequently used in ORT (40 studies out of 67). In the HDT, the examiner sits in the passenger seat, which has an operator function (i.e., a steering wheel and a pedal), and the subject drives 100 km on a highway at a speed of 95 km/h.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used drug was zopiclone. Because a significant deterioration of driving skill after ingestion has been recognized, zopiclone was commonly used as a comparative control when investigating hypnotics. Amitriptyline, which has also been shown to affect driving skill, was commonly used as a positive control for antidepressants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While zolpidem was deemed safer following bedtime use, middle-of-the-night administration showed this medication can also impair driving performance the morning after [10, 12]. It is important to bear in mind that, whereas the majority of these trials included only healthy young adults, other studies with middle-aged and elderly drivers have also shown similar findings [11, 15]. …”
Section: Discussionmentioning
confidence: 99%